+0  
 
0
165
2
avatar

How would I simplify this expression without having any negative exponents in my solution?

 

5•2-3t/40

 Jul 2, 2019
 #1
avatar+106539 
+1

[ 5 * 2-3t ] / 40  =

 

(5/40) * (2)-3t

 

(1/8) * ( 2)-3t  =

 

(2)-3  * (2)-3t  =

 

2 -3 - 3t  =

 

2 - (3 + 3t)  =      

 

 

     1                    1                        1

_______  =      _______    =      ______ 

   23 + 3t             (23) (1 + t)              8 1 + t

 

 

cool cool cool

 Jul 2, 2019
 #2
avatar
+1

Much appreciated! smiley

Guest Jul 2, 2019

29 Online Users